(untitled) (Al-Aasar, 2025)
This study presents a critical examination of the themes of bodily autonomy and existential anxiety in Urdu women’s novels through contemporary theoretical perspectives. The primary objective of the research is to explore how issues related to women’s bodies, sexuality, and individual agency are represented in Urdu fictional literature, and how these themes are linked to experiences of existential anxiety within the current social, cultural, and psychological contexts.The study provides a detailed analysis of female characters’ bodily autonomy, their struggles against social restrictions, and reflections of psychological crises in selected novels. Contemporary critical theories, including feminism, existentialism, and body theory, are employed to understand the complex relationship between women’s bodies and self-awareness. The research also demonstrates that bodily autonomy in Urdu women’s literature is not limited to physical boundaries but is deeply intertwined with social pressures, identity, and personal freedom.The findings reveal that female characters often experience deprivation of full bodily and personal autonomy due to social traditions, religious and cultural pressures, and caste or gender-based discrimination. The existential anxiety arising from such deprivation and constraints is prominently reflected in the narrative structure, character development, and storytelling techniques of the novels. Moreover, the study highlights that the themes of bodily autonomy and existential anxiety in Urdu women’s fiction not only mirror individual psychological and corporeal experiences but also promote awareness of social justice, gender equality, and women’s agency.This research integrates theoretical and practical perspectives in analyzing Urdu women’s literature and establishes a critical connection between global debates on feminism and existentialism and the literary representation of women’s bodily and psychological autonomy. It addresses gaps in Urdu literary studies and provides a scholarly foundation for critical discussions on existential and bodily freedom in women’s literature.